Pixel feature-weighted scale-adaptive object tracking algorithm - Hui-lan LUO; Fang-fang DU; Fan-sheng KONG (Tongxin xuebao)
An effective object tracking method using weighted pixel features was proposed to deal with all kinds of complicated tracking situations,such as target movement,rotation,background interference and scaling and so on.First,the color feature and location information of the pixels in the target area were used to build the object model.Then the average weight image was used to estimate the scale variation coefficient.The aim was to adapt to the scale changes of the target.Finally,an update model was proposed,which was able to renew the object model and background model.The experimental results show that the proposed algorithm could make full use of the differences between pixels in the target area,so it can track more quickly and more effectively with strong robustness.